Canariphantes junipericola - Borges, Paulo A. V. (2021)
JUSTIFICATION: Canariphantes junipericola is a single-island endemic species restricted to Flores (Azores, Portugal) (Crespo et al. 2014). It has a very small Extent of Occurrence (EOO = 4-12 km²) and Area of Occupancy (AOO = 4-12 km²), but the value is assumed to be at the upper end of this estimate. The species is rare and only known from a single subpopulation in the Natural Forest Reserve of Caldeiras Funda e Rasa. The surrounding area is highly invaded by alien plants. In the past, the species has probably strongly declined due to changes in habitat size and quality. Currently, invasive plants are changing some of the areas and decreasing the quality of the habitat. Based on Ferreira et al. (2016) the habitat will further decline as a consequence of climate change. Therefore, we suggest as future measures of conservation: (1) regular monitoring of the species; and (2) control of invasive plant species. Based upon the small geographic range of the species and continuing decline of its habitat area and quality, it is assessed as Critically Endangered.